Magnetic Sensing with Ferrofluid and Fiber Optic Connectors - Homa, Daniel (MDPI, 2014)
A simple, cost effective and sensitive fiber optic magnetic sensor fabricated with ferrofluid and commercially available fiber optic components is described in this paper. The system uses a ferrofluid infiltrated extrinsic Fabry-Perot interferometer (EFPI) interrogated with an infrared wavelength spectrometer to measure magnetic flux density. The entire sensing system was developed with commercially available components so it can be easily and economically reproduced in large quantities. The device was tested with two different ferrofluid types over a range of magnetic flux densities to verify performance. The sensors readily detected magnetic flux densities in the range of 0.5 mT to 12.0 mT with measurement sensitivities in the range of 0.3 to 2.3 nm/mT depending on ferrofluid type. Assuming a conservative wavelength resolution of 0.1 nm for state of the art EFPI detection abilities, the estimated achievable measurement resolution is on the order 0.04 mT. The inherent small size and basic structure complimented with the fabrication ease make it well-suited for a wide array of research, industrial, educational and military applications.